Dampak Positif Pandemi Covid-19 Meningkatkan Mutu Kompetensi Dosen Millennial IAHN Gde Pudja Mataram - Ida Bagus Alit Arta Wiguna (IAHN Gde Pudja Mataram, 2022)
Covid-19 pandemic in July 2021 was in its highest chart phase, so policymakers made rules for the implementation of restrictions on emergency community activities. This study aims to determine the positive impact of the Covid-19 pandemic for lecturers at IAHN Gde Pudja Mataram. By used a descriptive research type method with a qualitative approach, which examines the positive impact of the Covid-19 pandemic to improve the quality of lecturers. Lecturers develop the potential of knowledge by renewing self-understanding and participating in webinars that are suitable for the teaching and learning process. Potential skills by learning the use and benefit of applications suitable for the implementation of learning and research. The potential for affection is to increase vigilance and continue to use health protocols as long as the Covid-19 pandemic is not over and foster an interest in learning that remains enthusiastic.